2010
DOI: 10.1016/j.jfms.2010.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein electrophoresis in 155 cats

Abstract: All serum protein electrophoresis (SPE) results obtained between 2002 and 2009 from clinical cases presented to the University of Bristol Feline Centre were examined retrospectively. One hundred and fifty-five results met the inclusion criteria. Signalment and final diagnoses were obtained from the case records. Clinical cases were classified as having normal or abnormal SPE results by comparison to reference intervals for SPE created using 77 clinically normal cats. Abnormal results were then further divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0
5

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 24 publications
5
53
0
5
Order By: Relevance
“…Seeing that the gamma region is composed predominantly of antibodies of the IgG type, higher concentrations of γ-globulins obtained in calves with chronic respiratory diseases may reflect the response of the organism to inflammation. Taylor et al (2010) indicated that the increases in globulin fractions, particularly of the γ-globulins are associated with chronic antigenic stimulation. Stockholm and Scott (2008) stated that decreased albumin and an increase in globulin concentrations is the most common pattern in animals subjected to inflammatory diseases, which reflect the compensatory reduction in albumin concentrations to maintain oncotic pressure and viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Seeing that the gamma region is composed predominantly of antibodies of the IgG type, higher concentrations of γ-globulins obtained in calves with chronic respiratory diseases may reflect the response of the organism to inflammation. Taylor et al (2010) indicated that the increases in globulin fractions, particularly of the γ-globulins are associated with chronic antigenic stimulation. Stockholm and Scott (2008) stated that decreased albumin and an increase in globulin concentrations is the most common pattern in animals subjected to inflammatory diseases, which reflect the compensatory reduction in albumin concentrations to maintain oncotic pressure and viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of FIP is complicated and the cat's clinical history together with results from several analyses including serology, PCR and postmortem analyses are often required before a definite diagnosis can be reached (Shelly et al, 1988;Hartmann et al, 2003;Addie et al, 2004Addie et al, , 2009Pratelli, 2008;Sharif et al, 2010;Taylor et al, 2010). Hematological and biochemical changes in FIP cases are not very specific, but ascites, increase in serum protein level, increase in bilirubin, decrease in hematocrit and decrease in A:G ratio are prominent (Addie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…20 While the qualitative analysis of immunoglobulins (IgA, IgG, IgM, IgD) and their κ and λ subunits by immunofixation of serum in agar gel was not performed, the presence of a narrow spike in the γ region on SPE is suggestive of monoclonal immunoglobulin production, particularly of IgG. 11 Thus, we suspect that immunoglobulin secretion by B-cell TILs generated the observed paraneoplastic monoclonal gammopathy.…”
Section: Discussionmentioning
confidence: 99%